A new genus and five new species of Diptilomiopidae (Acari: Eriophyoidea) from south China - Wei, Sui-Gai; Wang, Guo-Quan; Li, De-Wei (Zootaxa, 2009)
A new genus and five new species of Diptilomiopidae are described and illustrated in this paper. Of these, three are in the Rhyncaphytoptinae: Scoliquadracus longipetiolatus n. gen. & n. sp. infesting Fagus longipetiolata Seem. (Fagaceae), Rhyncaphytoptus brassaiopsus n. sp. infesting Brassaiopsis glomerulata (Bl.) Regel (Araliaceae), and Rhyncaphytoptus debregeasus n. sp. infesting Debregeasia elliptica C. J. Chen (Urticaceae); and two are in the Diptilomiopinae: Apodiptacus archiboehmerus n. sp. infesting Archiboehmeria atrata (Gagnep.) C. J. Chen (Urticaceae), and Trimeroptes lambertianus n. sp. infesting Rubus lambertianus Ser. (Rosaceae).